Effect of different C3-aryl substituents on the antioxidant activity of 4-hydroxycoumarin derivatives - Rodríguez, Sergio Antonio (2011)
The antioxidant activity of 4-hydroxycoumarin synthetic derivatives and 4-methylumbelliferone were determined taking 4-hydroxycoumarin as the reference compound. Six 3-aryl-4-hydroxycoumarin derivatives were synthesized from 4-hydroxycoumarin as precursor in order to evaluate changes in their antioxidant properties due to C3-aryl substituent nature. Free radical scavenging capacities of these compounds against two different species DPPH and ABTS+ and the protecting ability towards the b-carotene-linoleic acid co-oxidation enzymatically induced by lipoxygenase were measured. In addition, the relationship between the activities of these molecules against DPPH radical and the bond dissociation energy of O-H (BDE) calculated using methods of computational chemistry was evaluated.